A Novel Single Cell RNA-seq Analysis of Non-Myeloid Circulating Cells in Late Sepsis - Darden, Dijoia B.; Dong, Xiaoru; Brusko, Maigan A.; Kelly, Lauren; Fenner, Brittany; Rincon, Jaimar C.; Dirain, Marvin L.; Ungaro, Ricardo; Nacionales, Dina C.; Gauthier, Marie; Kladde, Michael; Brusko, Todd M.; et al. (Frontiers in Immunology, 2021)
Background With the successful implementation of the Surviving Sepsis Campaign guidelines, post-sepsis in-hospital mortality to sepsis continues to decrease. Those who acutely survive surgical sepsis will either rapidly recover or develop a chronic critical illness (CCI). CCI is associated with adverse long-term outcomes and 1-year mortality. Although the pathobiology of CCI remains undefined, emerging evidence suggests a post-sepsis state of pathologic myeloid activation, inducing suboptimal lymphopoiesis and erythropoiesis, as well as downstream leukocyte dysfunction. Our goal was to use single-cell RNA sequencing (scRNA-seq) to perform a detailed transcriptomic analysis of lymphoid-derived leukocytes to better understand the pathology of late sepsis. Methods A mixture of whole blood myeloid-enriched and Ficoll-enriched peripheral blood mononuclear cells from four late septic patients (post-sepsis day 14-21) and five healthy subjects underwent Cellular Indexing of Transcriptomes and Epitopes by Sequencing (CITE-seq). Results We identified unique transcriptomic patterns for multiple circulating immune cell subtypes, including B- and CD4+, CD8+, activated CD4+ and activated CD8+ T-lymphocytes, as well as natural killer (NK), NKT, and plasmacytoid dendritic cells in late sepsis patients. Analysis demonstrated that the circulating lymphoid cells maintained a transcriptome reflecting immunosuppression and low-grade inflammation. We also identified transcriptomic differences between patients with bacterial versus fungal sepsis, such as greater expression of cytotoxic genes among CD8+ T-lymphocytes in late bacterial sepsis. Conclusion Circulating non-myeloid cells display a unique transcriptomic pattern late after sepsis. Non-myeloid leukocytes in particular reveal a host endotype of inflammation, immunosuppression, and dysfunction, suggesting a role for precision medicine-guided immunomodulatory therapy.